The type of involuntary overtime and emotional exhaustion among Chinese medical staff: The mediating role of job stress and moderated mediation role of desire for control in Machiavellian leadership - Cai, Han; Jin, Xiu (Nurture, 2023)
Purpose: With the development of China’s economy, China’s medical level is also rising. Medical staff is constantly working overtime due to heavy workload, which can lead to emotional exhaustion in the long run. Therefore, it is necessary to reduce the level of emotional exhaustion of Chinese medical staff. Based on this question, this study used involuntary overtime (conformity/workload) of medical staff working in Chinese medical institutions as an independent variable, trying to explore which variables increased the level of emotional exhaustion of medical staff. Design/Methodology/Approach: This study also investigated the mediating effect of job stress and the moderated mediating role of the desire for control in Machiavellian leadership. To investigate these questions, this study surveyed 313 medical personnel working in Chinese medical institutions. Findings: The results showed that involuntary overtime (conformity/workload) had a positive effect on job stress. work stress had no significant effect on emotional exhaustion. Job stress has a positive effect on emotional exhaustion of Chinese medical staff. Conclusion: This study aimed to identify which variables increase the level of emotional exhaustion in healthcare workers and suggested how to reduce emotional exhaustion in health care workers based on the findings. Research Limitations/Implications: We conducted a cross-sectional study. In future research, to further clarify these results, longitudinal studies should be conducted around the time gap. Practical Implications: Due to the unique nature of medical work, medical staff generally have unhealthy living habits. The organization should therefore reasonably arrange overtime for medical staff and appropriately allocate their workload. Additionally, Organizations should focus on the work-family situation of medical staff, improve their work enthusiasm, and reduce the occurrence of job stress. Contribution to Literature: This research expends the research field of overtime work types and emotional exhaustion.